The Behavior of Elevated Water Tanks under Impact Loading - Tavakoli, Davoud; Ahmadi, Ali (Periodica Polytechnica Civil Engineering, 2021)
Because of the crucial role of elevated water tanks and their various uses, it is necessary to evaluate their structural behavior under threats to improve the durability performance of such tanks without putting them in jeopardy. In the present research, three open cylindrical concrete water tanks were modeled under an impact load (aerial blast) with the weight of 100 kg TNT explosive charge. The tanks were modeled in 3 forms: slender, middle, and broad (Aspect ratio =28,1 and 0.85). Each tank contained various levels of water (non-water, half water, and full water) to estimate their structural behavior under blast loading. Moreover, the CEL (Coupled Eulerian-Lagrangian) approach was used to simulate water structure interaction in finite element program. For a comprehensive analysis of the structural behavior of water tanks, LRB (Lead rubber bearing) isolator device was also used to observe the effect of isolator under blast loading on elevated water tanks in all models. The results of this study show that the water level leads to stiffness of the structures that cause better performance under blast loading and also the intersection of the shaft and concrete column would be the critical section of this structure under blast loading. It is also concluded that Stress and Strain decrease as the water tanks level increase and stiffen (up to 33 %). Also, it is noticeable that the existence of the isolator has deteriorated the results because of the decreases in the structure’s stiffness and the increase of the displacements.